2021
DOI: 10.3389/fnins.2021.668616
|View full text |Cite
|
Sign up to set email alerts
|

Determining 5HT7R’s Involvement in Modifying the Antihyperalgesic Effects of Electroacupuncture on Rats With Recurrent Migraine

Abstract: Electroacupuncture (EA) is widely used in clinical practice to relieve migraine pain. 5-HT7 receptor (5-HT7R) has been reported to play an excitatory role in neuronal systems and regulate hyperalgesic pain and neurogenic inflammation. 5-HT7R could influence phosphorylation of protein kinase A (PKA)- or extracellular signal-regulated kinase1/2 (ERK1/2)-mediated signaling pathways, which mediate sensitization of nociceptive neurons via interacting with cyclic adenosine monophosphate (cAMP). In this study, we eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 108 publications
1
19
0
Order By: Relevance
“…Moreover, dural inflammation is considered to be the cause of activation of trigeminal neurovascular system ( Débora et al, 2016 ). Studies have shown that the injection of inflammation soup through the dura mater could induce hyperalgesia in rats, causing meningeal neurogenic inflammatory pain sensitivity migraine and significantly reducing the mechanical pain threshold in rats ( Liu et al, 2021 ; Olivia et al, 2021 ). According to the results obtained in this study, the pain threshold of rats was significantly reduced after 2 weeks of modeling with inflammation soup.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, dural inflammation is considered to be the cause of activation of trigeminal neurovascular system ( Débora et al, 2016 ). Studies have shown that the injection of inflammation soup through the dura mater could induce hyperalgesia in rats, causing meningeal neurogenic inflammatory pain sensitivity migraine and significantly reducing the mechanical pain threshold in rats ( Liu et al, 2021 ; Olivia et al, 2021 ). According to the results obtained in this study, the pain threshold of rats was significantly reduced after 2 weeks of modeling with inflammation soup.…”
Section: Discussionmentioning
confidence: 99%
“…The pain thresholdTRPV1 of frontal muscle and bilateral posterior temporal muscle was significantly reduced in migraine patients ( Rogers et al, 2020 ). Pharmacological experiments showed that the mechanical pain threshold of rats with migraine was significantly reduced ( Liu et al, 2021 ). The results of this study are consistent with these results reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some other notable findings are the changes at the cellular level, and we have summarized all the below findings in supplementary tables , notably the effects in TG ( supplementary Table S1 ), brain/spinal cord ( supplementary Table S2 ) and TNC ( supplementary Table S3 ). The levels of c-Fos, a marker of neuronal activation and nociception, have been observed at higher expression levels in the TG and TNC [ 63 , 64 , 65 ]. Increases of other nociceptive and neuronal activation markers in the TGVS have been observed, such as increases in cAMP [ 64 ], PKA [ 64 ], ERK 1/2 [ 64 ], CREB [ 64 ], NGF [ 66 ], PKC [ 66 ], tyrosine receptor kinase B (TrkB) [ 67 ] and EAAT3 [ 67 ].…”
Section: The Inflammatory Soup (Is) Model and Its Variantsmentioning
confidence: 99%
“…The levels of c-Fos, a marker of neuronal activation and nociception, have been observed at higher expression levels in the TG and TNC [ 63 , 64 , 65 ]. Increases of other nociceptive and neuronal activation markers in the TGVS have been observed, such as increases in cAMP [ 64 ], PKA [ 64 ], ERK 1/2 [ 64 ], CREB [ 64 ], NGF [ 66 ], PKC [ 66 ], tyrosine receptor kinase B (TrkB) [ 67 ] and EAAT3 [ 67 ]. Increases of inflammatory markers have also been observed in the TGVS, notably an increase in IL-1β [ 65 , 68 ], IL-18 [ 69 ], TNF-α [ 65 , 70 ], p38 [ 67 ], BDNF [ 67 ], Iκβ [ 71 ], TRIF [ 71 ], TLR4 [ 71 ], Myd88 [ 71 ] and NF-κβ [ 71 ], FKN [ 72 ], CX3CR1 [ 72 ] and PGE 2 [ 73 ].…”
Section: The Inflammatory Soup (Is) Model and Its Variantsmentioning
confidence: 99%